2′-Deoxyribonolactone lesion produces G→A transitions in Escherichia coli - Faure, Virginie (Oxford University Press, 2004)
2′-Deoxyribonolactone (dL) is a C1′-oxidized abasic site damage generated by a radical attack on DNA. Numerous genotoxic agents have been shown to produce dL including UV and γ-irradiation, ene-dye antibiotics etc. At present the biological consequences of dL present in DNA have been poorly documented, mainly due to the lack of method for introducing the lesion in oligonucleotides. We have recently designed a synthesis of dL which allowed investigation of the mutagenicity of dL in Escherichia coli by using a genetic reversion assay. The lesion was site-specifically incorporated in a double-stranded bacteriophage vector M13G*1, which detects single-base-pair substitutions at position 141 of the lacZα gene by a change in plaque color. In E.coli JM105 the dL-induced reversion frequency was 4.7 × 10(–5), similar to that of the classic abasic site 2′-deoxyribose (dR). Here we report that a dL residue in a duplex DNA codes mainly for thymidine. The processing of dL in vivo was investigated by measuring lesion-induced mutation frequencies in DNA repair deficient E.coli strains. We showed a 32-fold increase in dL-induced reversion rate in AP endonuclease deficient (xth nfo) mutant compared with wild-type strain, indicating that the Xth and Nfo AP endonucleases participate in dL repair in vivo.